2010
DOI: 10.1007/978-3-642-12242-2_39
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Sound Synthesis: Rendering Spectrograms from Cellular Automata Histograms

Abstract: Abstract. In this paper we report on the synthesis of sounds using cellular automata, specifically the multitype voter model. The mapping process adopted is based on digital signal processing analysis of automata evolutions and consists in mapping histograms onto spectrograms. The main problem of cellular automata is the difficulty of control and, consequently, sound synthesis methods based on these computational models normally present a high factor of randomness in the output. We have achieved a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The implementation is done by MatLab to produce an output spectrum according to input (target) sound spectrum file. Other researchers [15] have been used method which is cellular automata (CA). This technique can be classified as one of a class of evolutionary algorithms for modeling dynamic systems that modify several characteristics with time.…”
Section: Evolutionary Sound Synthesismentioning
confidence: 99%
“…The implementation is done by MatLab to produce an output spectrum according to input (target) sound spectrum file. Other researchers [15] have been used method which is cellular automata (CA). This technique can be classified as one of a class of evolutionary algorithms for modeling dynamic systems that modify several characteristics with time.…”
Section: Evolutionary Sound Synthesismentioning
confidence: 99%
“…The growth model used in this research is the one we developed in [9] as an extended version of the multitype voter model.…”
Section: Ca Growth Modelmentioning
confidence: 99%
“…This search for input parameters is then a good candidate for an automatic optimization scheme. Thus, diverse optimization methods have been used for automatic calibration, such as Particle Swarm [11], HMM [34], Neural Nets [27], Cellular Automata [29] and Genetic Algorithms [12]. It has been suggested that evolutionary approaches such as Genetic Algorithms (GAs) are performing the best to matching musical instrument tones [27].…”
Section: Introductionmentioning
confidence: 99%